The Associations of Two Novel Inflammation Indexes, SII and SIRI with the Risks for Cardiovascular Diseases and All-Cause Mortality: A Ten-Year Follow-Up Study in 85,154 Individuals - Jin Z; Wu Q; Chen S; Gao J; Li X; Zhang X; Zhou Y; He D; Cheng Z; Zhu Y; Wu S (Dove Medical Press, 2021)
Ziqi Jin,1,* Qiong Wu,1,* Shuohua Chen,2,* Jingli Gao,3 Xiaolan Li,3 Xuhui Zhang,4 Yaohan Zhou,1 Di He,1 Zongxue Cheng,1 Yimin Zhu,1,5,6 Shouling Wu7 1Department of Epidemiology & Biostatistics, School of Public Health, Zhejiang University, Hangzhou 310058, Zhejiang, People’s Republic of China; 2Health Care Center, Kailuan Group, Tangshan 063000, People’s Republic of China; 3Department of Intensive Medicine, Kailuan General Hospital, Tangshan 063000, People’s Republic of China; 4Hangzhou Center for Disease Control and Prevention, Hangzhou 310051, Zhejiang, People’s Republic of China; 5Department of Respiratory Diseases, Sir Run Run Shaw Hospital Affiliated to School of Medicine, Zhejiang University, Hangzhou, Zhejiang 310060, People’s Republic of China; 6Department of Pathology, School of Medicine, Zhejiang University, Hangzhou 310058, Zhejiang, People’s Republic of China; 7Department of Cardiology, Kailuan General Hospital, Tangshan, 063000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Shouling WuDepartment of Cardiology, Kailuan General Hospital, 57 Xinhua East Road, Tangshan, People’s Republic of ChinaEmail drwusl@163.comYimin ZhuDepartment of Epidemiology & Biostatistics, School of Public Health, Zhejiang University, 388 Yu-Hang-Tang Road, Hangzhou, 310058 Zhejiang, People’s Republic of ChinaTel + 0086-571-88208194Email zhuym@zju.edu.cnBackground: SII and SIRI are two novel systemic inflammation indexes that were suggested in predicting poor outcomes in cancers. However, no studies have examined their effect on cardiovascular diseases (CVDs) and all-cause mortality. Thus, this study aims to investigate associations between SII, SIRI, and the risks for CVDs and all-cause mortality.Methods: A total of 85,154 participants from the Kailuan cohort were included and followed up for incidents of CVDs (including MI, stroke) and all-cause death for 10 years. Multiple Cox regression was used to calculate the adjusted hazard ratios (HRs).Results: During the follow-up period, 4262 stroke events, 1233 MI events, and 7225 all-cause deaths were identified, respectively. Compared with the lowest quantile (Q1) of SII or SIRI, after adjusted for most cardiovascular risk factors, both indexes showed positive associations with the risk for stroke (adjusted HRs in Q4 were 1.264 (95% CI: 1.157,1.382) for SII, 1.194 (95% CI: 1.087,1.313) for SIRI), and all-cause death (adjusted HRs in Q4 were 1.246 (95% CI: 1.165,1.331) for SII, 1.393 (95% CI: 1.296,1.498) for SIRI). Additionally, higher SII and SIRI are also associated with increased risk of hemorrhagic stroke and ischemic stroke. Higher SIRI but not SII exhibited a higher MI risk, the adjusted HR in Q4 was 1.204 (1.013,1.431). The significant association remained after additional adjustment for CRP. Subgroup analysis and sensitivity analysis displayed consistent results except for SIRI with MI, where the association did not arrive at significance in subjects aged ≥ 60.Conclusion: Elevated SII and SIRI increased the risk of stroke, two stroke subtypes, and all-cause death. Higher SIRI, but not SII associated with increased MI incidence, and the association of SIRI was only significant in subjects aged < 60.Keywords: systemic inflammation, prospective study, risk factors, cardiovascular events, mortality